Wrinkle wise mist / Ikmal Arief Johari ... [et al.] - Johari, Ikmal Arief; Rozli, Hana Najihah; Sidek, Nuranisah Hidayati; Nawi, Nur Amalia Ayunni; Mohd Roslan, Nurul Najjah Najihah; Muhamad Sharil, Siti Nurmarshiela (2023)
Our new product development effort introduces the Wrinkle Wise Mist, an inventive gadget that aims to revolutionise the way we take care of our clothes in response to the growing demand for creative solutions in the field of garment care. With this state-of-the-art tool, you can effortlessly combine steaming clothes with cutting-edge humidification technology to get a two-fold solution that tackles the nagging problem of creases and refreshes clothes. The Wrinkle Wise Mist uses ultrasonic technology to produce a fine mist that efficiently lessens wrinkles on clothes without compromising the integrity of the fabric. This appliance not only makes clothes appear perfectly ironed, but it also adds a soft touch to shield them from harm. It's a really practical and versatile piece of equipment for people who desire efficient and long-lasting clothing because of its user-friendly features. According to our market analysis, there is a big need in the laundry care sector for a complete solution that improves fabric health in addition to getting rid of wrinkles. The Wrinkle Wise Mist is positioned to take advantage of this chance by providing a special and effective way to maintain clothes. Our product is in line with changing consumer expectations as there is a greater emphasis on long-lasting clothing and ecological fashion. Wrinkle Wise Mist’s major target market consists of people who value well-maintained clothing, busy professionals, and fashion enthusiasts. This gadget serves those looking for a quick and easy way to clean their clothes without sacrificing the fit and beauty of their clothes. Due to its adaptability, it can be worn by a wide range of people and with different kinds of fabrics and styles of clothing. Our invention stands out from the competition by expertly fusing two necessary features—wrinkle removal and clothing steaming—into a single, streamlined apparatus. With its cutting-edge approach to clothing care, the Wrinkle Wise Mist gives businesses a competitive edge and establishes itself as a high-end option for customers who value convenience and fashionable clothes. Its modern appearance and cutting-edge technology add to its allure in a crowded market.